Dietary Diversity and Its Contribution in the Etiology of Maternal Anemia in Conflict Hit Mount Cameroon Area: A Cross-Sectional Study - Jugha, Vanessa Tita; Anchang-Kimbi, Judith Kuoh; Anchang, Juliana Adjem; Mbeng, Kennedy Aminde; Kimbi, Helen Kuokuo (Frontiers in Nutrition, 2021)
Background In the Mount Cameroon area, maternal anaemia remains a major public health concern. We hypothesized that nutrient inadequacy may account for the level of anaemia in pregnancy. Thus, this study examined the relative effect of dietary diversity on maternal anaemia in the study area. Methods: A total of 1,014 consenting pregnant women were enrolled in this cross-sectional study. Information on socio-demographic, antenatal characteristics, malaria and anaemia control measures were documented. Dietary diversity (DD) was evaluated using the 24-hour recall method and haemoglobin (Hb) levels (g/dl) measured using a portable Hb meter. Malaria parasitaemia was diagnosed by blood microscopy. Anaemia status was trimester specific. Logistic regression analysis was used determine predictors of maternal anaemia. Results: Among the pregnant women enrolled, the mean DD score was 3.5±0.8 SD and only 10.4% had adequate dietary diversity. Anaemia prevalence was 40.9%. Majority of the women consumed starchy staples (99.3%) while least consumed foods were dairy (4.5%), eggs (8.3%), fruits and vegetable (vitamin A-rich) (8.6%). A significant lower prevalence of anaemia was associated with intake of dairy (P < 0.001), animal protein (P = 0.006), vitamin A-rich fruits and vegetables (P < 0.001). Furthermore, mean Hb levels were higher (P < 0.001) among women with diverse diets (12.39 ± 1.34) than in those with less diverse diets (10.85 ± 1.33). Predictors of anaemia were as follows: study setting (Odd Ratio (OR)= 1.4, 95% CI: 1.07-1.94), occupation (OR= 1.9, 95% CI: 1.16-3.43), number of clinic visits (OR= 1.9, 95% CI: 1.27-2.91), trimester of pregnancy (OR= 3.2, 95% CI: 1.45-7.38), malaria parasitaemia (OR= 1.8, 95% CI: 1.33-2.68), out of home eating (OR= 1.4, 95% CI: 1.03-2.13) and DD (OR= 9.8, 95% CI: 4.56-20.80). The attributable risk of anaemia due to dietary diversity was 82.9%. Conclusion: In the study area, DD is a major risk factor for maternal anaemia. This finding underscores the importance of content specific nutrition education during clinic visits to improve intake of protein and iron-rich food in anaemia prevention.